Genomics education in nursing in Hong Kong, Taiwan and Mainland China. (17th July 2019) - Chair, Sek Ying; Waye, Mary Miu Yee; Calzone, Kathleen; Chan, Carmen Wing Han
Abstract : Aim: To identify issues and challenges of genomics education in Hong Kong, Taiwan and Mainland China. Background: The use of genetics/genomics in health care, such as genetic testing, pharmacogenomics and tumour profiling in the context of cancer, is increasing. The rapid application of genetics/genomics in clinical practice requires healthcare providers to be competent to practise genetics‐related patient care. Sources of evidence: We reviewed current practices in genomics education in nursing in Hong Kong, Taiwan and Mainland China, including the opportunities for nurses to advance their knowledge and recommendations to incorporate genomics education in the nursing curriculum in these regions. Findings: While many citizens and health professionals recognize the importance of new and exciting research areas of genomics/genetics, there are still many gaps in the translation of genetic/genomic medicine into clinical practice. There is also a similar lack of genetics professionals in China. Conclusion: Hong Kong, Taiwan and Mainland China face challenges in promoting genetic education in nursing. A strategic approach in a coordinated effort ineffectively translating genomic knowledge into healthcare practice should be established in these three regions. Implications for nursing and policy: Nursing educators in Hong Kong, Taiwan and Mainland China should link with the international nursing community (e.g. Global Genomics Nursing Alliance) and form closer networks to improve education in the area of genetics and genomics. From a policy level, genomics education is suggested to be incorporated in nursing curriculum to enhance nurses' competency in incorporating genetics/genomics service into patient care.